The Effect of E-FAS on the Knowledge of Post-partum - Rosidah Solihah; Ayu Endang Purwati; Sri Utami Asmarani (Genius Journal, 2023)
Introduction: The postpartum period is a period of recovery of the uterine organs as before pregnancy, the recovery time is around 6-8 weeks. Physical and mental changes will experience different changes that can disrupt daily activities. Several types of complications that may occur include physical, mental and emotional problems, for example fatigue, decreased sexual relations, anxiety, constipation, breastfeeding problems, sleep disorders, bleeding and difficulty urinating. Objective: The aim of this research was to determine the effect of E-FAS on the knowledge of postpartum mothers at the Khasanah Panumbangan Clinic. Method: This research design uses the Quasy experimental method with pretest and posttest. This research design takes the form of a non-equivalent control group design. The research subjects were 30 postpartum mothers at the Khasanah Clinic, Panumbangan District, Ciamis Regency. This research instrument uses a questionnaire to determine the knowledge of postpartum mothers. Data analysis used the Wilcoxon Test to see the effect of E-FAS on increasing the knowledge of postpartum mothers. Result: the results of statistical analysis with an average ranking value of 10.50 while the number of positive rankings or sum of rank was 210. There were 10 people with the same score before being given E FAS and after being given E FAS. The Wilcoxon test obtained a p value of 0.000 (<0.005) so it can be concluded that there is an influence of E FAS on the knowledge of postpartum mothers at the Khasanah Clinic, Panumbangan District. Conclusion: E-FAS can be used as a medium for health information, especially in midwifery care after childbirth and breastfeeding.